Vascular Aging in Ischemic Stroke - Lian Liu; Bo Zhao; Yueyang Yu; Wenwei Gao; Weitu Liu; Lili Chen; Zhongyuan Xia; Quan Cao (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Cellular senescence, a permanent halt in cell division due to stress, spurs functional and structural changes, contributing to vascular aging characterized by endothelial dysfunction and vascular remodeling. This process raises the risk of ischemic stroke (IS) in older individuals, with its mechanisms still not completely understood despite ongoing research efforts. In this review, we have analyzed the impact of vascular aging on increasing susceptibility and exacerbating the pathology of IS. We have emphasized the detrimental effects of endothelial dysfunction and vascular remodeling influenced by oxidative stress and inflammatory response on vascular aging and IS. Our goal is to aid the understanding of vascular aging and IS pathogenesis, particularly benefiting older adults with high risk of IS.